1997
DOI: 10.2494/photopolymer.10.409
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Characteristics of Chemically Amplified DUV Resists.

Abstract: Dissolution kinetics of a chemically amplified deep ultraviolet (DUV) positive resist, which consists of tert-butoxycarbonyl (t-BOC) protected phenolic resin, benzenesulfonic acid derivative as a photoacid generator (PAG) and an additional dissolution inhibitor, has been investigated by focusing on the polymer structures (t-BOC blocking level, molecular weight and molecular weight dispersion) and photo-acid structures. Based on the analysis of the dissolution rate curve and Arrhenius plots, it was concluded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 7 publications
0
21
1
3
Order By: Relevance
“…Acid concentrations are not treated as constant, but undergo continuous reduction through loss processes. Simpler treatments involve the analysis of ionic conductivities [25][26][27] or material loss after development as a function of baking conditions [20,24]. The diffusion coefficients reported in all of these studies are difficult to compare with one another directly because of the differences in polymer, photoacid generator (PAG) type and concentration, post-application bake (PAB) conditions, and PEB temperatures used; they range from 10 Ϫ15 to 10 Ϫ11 cm 2 /s.…”
Section: Literature On Image Spreading In Positive-tone Ca Resistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid concentrations are not treated as constant, but undergo continuous reduction through loss processes. Simpler treatments involve the analysis of ionic conductivities [25][26][27] or material loss after development as a function of baking conditions [20,24]. The diffusion coefficients reported in all of these studies are difficult to compare with one another directly because of the differences in polymer, photoacid generator (PAG) type and concentration, post-application bake (PAB) conditions, and PEB temperatures used; they range from 10 Ϫ15 to 10 Ϫ11 cm 2 /s.…”
Section: Literature On Image Spreading In Positive-tone Ca Resistsmentioning
confidence: 99%
“…As noted above, because diffusion is accompanied by reaction, the extraction of diffusion kinetics independent of deprotection kinetics is not simple. Numerous investigations of acid diffusion in positive-tone chemically amplified resist systems have been reported using the following to elucidate the coupled reaction-diffusion process: multilayer structures of acidified polymer or a layer of pure acid on pure polymer [20 -22]; linewidth measurements [23,24]; ionic conductivities [23,[25][26][27]; and spectroscopic probes of polymer chemistry changes during or after post-exposure bake [22, 23, 28 -30]. Diffusion coefficients are typically obtained from the experimental measurements in one of three ways.…”
Section: Literature On Image Spreading In Positive-tone Ca Resistsmentioning
confidence: 99%
“…Simulations [5] have also predicted the same, and this has been justified in terms of the acid diffusion, which softens the difference in exposure between neighboring regions of the resist line to the intermediate region between exposed and un-exposed film. It has been reported that the use of low molecular weight and low dispersivity polymers as resist films decreases roughness and acid diffusion range [39]. Also, the use of low dispersivity polymer films results in smoother side surface and the acid diffusion range can be extended into greater values with acceptable distortions in the final image [33].…”
Section: Resist Film Surface and Line-edge Roughnessmentioning
confidence: 98%
“…Many research groups tried to investigate the dissolution characteristics of chemically amplified DUV resists [14][15]. In our previous report, poly [4-hydroxystyreneco-4-(3-cyano-1,5-di-tert-butyl carbonyl pentyl styrene)] (PHSCBPS) was synthesized and blended with poly(4-hydroxystyrene-co-4-(1-ethylethoxystyrene)) (EEPHS) to understand how the dissolution rate of blended resin can affect the pattern profile of resist [9].…”
Section: Effect Of Second Blocking Group Into Eephs On Dissolution Ramentioning
confidence: 99%